2020
DOI: 10.1002/ldr.3841
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and regional differences in ecosystem services responses driven by the “Three Modernizations”

Abstract: Strengthened anthropogenic activities significantly modify ecosystem services (ES), while there are differences in impacts on ES from various anthropogenic activities. In the literature a specific focus on addressing the spatial heterogeneity of comprehensively measured anthropogenic activities on ES is lacking. From an integrated perspective of the "Three Modernizations", that is: 1) agricultural modernization (AM); 2) industrialization and: 3) urbanization, this article aimed to investigate the heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Changes in the natural climate are also factor which affect ecosystem services. Research has shown that among the factors of influence, such as surface morphology, precipitation, soil erodibility and relevant management policies and measures, the amount of precipitation had a relatively severe effect on soil conservation and water yield [ 46 , 47 ]. The management policies and measures related to human activities had less impact, while the surface morphology and soil erodibility had greater impact on the soil conservation function, among which the rate of coverage of surface vegetation was one of the most important factors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the natural climate are also factor which affect ecosystem services. Research has shown that among the factors of influence, such as surface morphology, precipitation, soil erodibility and relevant management policies and measures, the amount of precipitation had a relatively severe effect on soil conservation and water yield [ 46 , 47 ]. The management policies and measures related to human activities had less impact, while the surface morphology and soil erodibility had greater impact on the soil conservation function, among which the rate of coverage of surface vegetation was one of the most important factors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is also a driving factor that affects ecosystem services. Studies have shown that among the impacts of precipitation, management policies, terrain, and soil erodibility on soil conservation and water production, the impact of precipitation was greater [6,23]. The management policies related to human activities had relatively little impact on those services, and terrain had a greater impact on soil conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Different researchers have achieved certain results in the study of the trade-offs and synergies of ecosystem services [23]. The general method is to analyze the relationship between different services by evaluating them and by subsequently putting forward suggestions to solve the main problems in the study area [24].…”
Section: Introductionmentioning
confidence: 99%
“…In China, Cao et al (2020) discuss ecological restoration's intersection with poverty alleviation, indicating its potential for sustainable outcomes. Tian et al (2020) investigate anthropogenic activities' repercussions on ecosystem services in Tibet, stressing the need for context‐aware ecological management. Li, Liu, et al (2021) report the impact of land use/cover changes on sediment retention services (SRS) in the Three Gorges Reservoir area (TGRA), China.…”
Section: Land Systems Ecosystem Services and Managementmentioning
confidence: 99%